PENGETAHUAN AKSEPTOR KB SUNTIK 3 BULANAN TENTANG EFEK SAMPING KB SUNTIK 3 BULANAN DI PUSKESMAS II KEMBARAN PURWOKERTO - Ikit Netra Wirakhmi; Erni Rokhani (Universitas Harapan Bangsa Purwokerto, 2010)
Background: The KB is a means of contraception to space pregnancies. Based on statistical data of 2008participants BKKBN family planning in Indonesia as many as 26,557,302 people. Of the total of allparticipants in Central Java KB KB susntik highest users of DMPA (33.50%). From preliminary studieson the health center II twins feel the side effects of family planning acceptors 3-month injectable form ofweight changes, spotting, vaginal discharge, headaches, acne. To determine the level of knowledge offamily planning acceptors 3 monthly injections of side effects on 3-month injectable acceptors in thehealth center II twins Navan Banyumas Year 2009. Methods: The study uses descriptive quantitative method with cross sectional approach, the technique ofprimary data collection instrument used is a questionnaire in which data collection techniques usingaccidental sampling rate of 35 respondents who used univariate analysis. Results: Research has shown that knowledge about the side effects kb acceptor 3 monthly injections inhealth centers is a good Navan II twins of 57% (20 respondents), based on 14 respondents aged 20-35years (53.8%), elementary education 7 respondents (50 %), employment IRT 11 respondents (52.4%),parity 2-4 12 respondents (52.1%), all in categories of good knowledge. Conclusion: Knowledge of mothers about the side effects of three monthly injections in family planninghealth center II twins purwokerto by age, education, occupation, parity result is good. Keywords: Knowledge, side effects 3-month injectable KB